Infestação da mosca-negra-dos-citros (Aleurocanthus woglumi Ashby) em pomares de citros, em sistemas de plantio convencional e agroflorestal - da Silva, Anderson Goncalves [UNESP]; Boica, Arlindo Leal [UNESP]; Silva Farias, Paulo Roberto; Barbosa, Jose Carlos [UNESP] (Soc Brasileira Fruticultura, 2011)
The purpose of this study was to evaluate the infestation of citrus blackfly in a citrus orchard in conventional tillage systems and agroforestry. The experimental area is located in the municipality of Capitao Poco, PA, where 12 samples were taken during the period from September 2008 to October 2009, evaluating the presence or absence of the pest in both production systems. The results showed that the system of agroforestry plantation showed higher incidence of plants with presence of citrus blackfly compared to the conventional, there was influence of temperature on the regulation of pest population and heavy rain reduced the number of plants with presence of A. woglumi.
Infestation of citrus blackfly in citrus orchards conventional and agroforestry
Keywords: Aleyrodidae; Citrus sinensis; Insecta; Agroforestry system; Tectona grandis; Aleurocanthus woglumi